Pengelolaan Pembelajaran Ilmu Pengetahuan Sosial Di Sekolah Dasar Negeri Jajar 1 Surakarta - Ngimatun, Siti An, Dr.Suyatmini,SE.,M.Si, Dr.Ahmad Fathoni, M. Pd (2016)
This study have three aims to describes: 1) planning of social science learning, 2) implementation of social cience learning, 3) evaluation of social science learning in State elementary school of Jajar 1 Surakarta. This research is qualitative research with etnography design. Data was collected by interview, observation, and ocumentation. Data analysis use Milles and Huberman analysis are data reduction, data display and verification. Results of this research there are three things about: 1) Planning of social science learning in State elementary school of Jajar 1 Surakarta are prepare learning materials at beginning semester, learning tools at least 1 week before learning, appropriate learning media both hardware and software. Teachers appeared as a co-sharing within the constraints of the lesson plan preparation. 2) mplementation of social science learning in State elementary school of Jajar 1 Surakarta begins with providing apperception, teachers convey comprehension the material through a power point and teaching aids. Electricity goes out make some learning facilities not maximal. The advantages of the use social sciences learning media is the recognition directly between the materials studied by the real conditions surrounding environment, both the elements of the economic, social, cultural or any other. Teachers coordinate with the school to apply for an additional teaching aids needed. 3) Evaluation of social studies learning in State elementary school of Jajar 1 Surakarta is done through the evaluation phase in the learning process and evaluation at the end of the lesson. Evaluation of social studies learning in written form includes multiple choice and essay and practice forms. Assessment is oriented to measure the cognitive, affective and psychomotor. Standard theoretical value should be obtained at least 70, while practices value at least 73.